Mengurangi Penggunaan Produk Kemasan Plastik Makanan Jajanan Siswa Sekolah Dasar 06 Ulak Karang Utara Padang - Linda Handayuni; Dewi Mardiawati; Berly Nisa Srimayarti (Jurnal Pengabdian Pada Masyarakat, 2021)
REDUCING THE USE OF PLASTIC PACKAGING PRODUCTS SNACK FOOD FOR ELEMENTARY SCHOOL STUDENTS 06 ULAK KARANG UTARA PADANG. School-age children are the generation of the nation's administrators, when they are of developmental age that require nutritional intake to improve good nutritional status. School children generally spend one third of their time at school, thus causing children the opportunity to buy food in the school area. Based on previous research, it was found that almost all respondents (98.7%), students had the habit of buying snacks at school, with the highest frequency of snacks being 2 times a day. Often food products are sold in plastic packaging, where the plastic packaging for food products that does not comply with the Indonesian National Standard has harmful contents for the body. Children buy snack food products based solely on their preferences without thinking that the snack food products are served in packaging made of plastic-based products that can cause illness for themselves. Community service is carried out through socializing the use of plastic packaging products on snacks for elementary school students. Data collection was carried out through observation, document study and interviews, at Elementary School 06 Ulak Karang Utara Padang from March to July 2019. Respondents consisted of 3rd grade students and street food vendors selling at Ulak Karang Utara 06 Elementary School, Padang. The form of activity is the socialization of the types of plastics and the negative impact of using plastic products for body health by using posters and brochures and implementing plastic waste management with the concept of 3R, Reuse, Reduce, Recycle.